DESIGN AND IMPLEMENTATION OF DIGITAL TV ANTENNA WITH RF AMPLIFICATION FOR CHANNELS 478-694 MHZ - Pitri, Putra Aditya; Suryadi, Dedy; Imansyah, Fitri (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2024)
Digital television is a device used to capture digital TV broadcasts, this type of television uses digital modulation and compression systems to broadcast image, sound, and data signals to television sets. The need for this technology requires a device that can work to carry out the digital TV communication function. One very important communication device is the antenna. B iquad antenna is a loop antenna with a rectangular contour and is paralleled to get a smaller impedance. Wireless communication is inseparable from the existence of antenna devices. This research only focuses on analyzing signal reception on digital TV frequencies 478-694 MHz and on antenna design. This research discusses the design of a digital TV antenna with an RF amplifier and analyzes the parameters of the antenna design results and optimizes the antenna design to fit specifications. Simulation results on CST studio show that the biquad antenna has a VSWR value of 1.64, return loss of -12.26 dB, bandwidth of 114.44 MHz, gain of 9.080 dBi, and directivity of 9.253 dBi. These parameter values are obtained after performing an optimization process from previous simulations that still do not meet specifications. In the correlation of digital TV, antennas with RF amplifiers are able to capture very good signal strength and quality on each channel on the digital TV screen so that good image quality is obtained.